Lipid Profile Alterations in Different Tissues of Channa punctatus, During Different Periods of Fasting and Refeeding - Dar, Zubair Shafi; Pawar, S.S.; Dongre, S.B.; A.Wani, Mashooq (International Journal of Scientific Research in Biological Sciences, 2022)
Many animals undergo starvation every year for environmental reasons. Animals respond to starvation by changing their biochemical and physiological systems in adaptive ways that trigger the loss of body weight due to a lack of food. The organism tries to conserve energy by reducing the number of calories. In this study, Channa punctatus was administered for fasting periods of 7, 14, 21, and 28 days and refeeding periods of 7, 14, 21, and 28 days. The findings confirmed that after 7 days of fasting, liver lipids depreciated but recovered after 7 days of refeeding. Mobilization of lipids occurs in the muscle tissue after 14 days, and these reserves begin to re-establish themselves after 21 days of refeeding. However, after starvation, the lipid content in the muscle, gills, and kidney was reported in decreasing order, and the lipid profile concentration level increased after 28 days of refeeding in these tissues. Notably, the alterations in the metabolism of lipids through these stages can be considered survival approaches used by Channa punctatus. The alteration in the metabolic profile of the tissues, that influences in the stages of fasting, and the types of assets mobilized were all evidence.